Effects of Metformin, Metformin Plus Rosiglitazone, and Metformin Plus Lifestyle on Insulin Sensitivity and β-Cell Function in TODAY (American Diabetes Association, 2013)
OBJECTIVE: The Treatment Options for type 2 Diabetes in Adolescents and Youth (TODAY) trial demonstrated that combination therapy with metformin plus rosiglitazone provided superior durability of glycemic control compared with metformin alone, with significantly lower treatment failure rates (38.6 vs. 51.7%), and metformin plus lifestyle was intermediate. Herein we describe the temporal changes in measures of β-cell function and insulin sensitivity over a 4-year period among the three treatments. RESEARCH DESIGN AND METHODS: TODAY participants (699) were tested periodically with an oral glucose tolerance test to determine insulin sensitivity (1/fasting insulin [1/I(F)]), insulinogenic index (△I(30)/△G(30)) or C-peptide index (△C(30)/△G(30)), and β-cell function relative to insulin sensitivity (oral disposition index [oDI]). RESULTS: During the first 6 months, metformin plus rosiglitazone exhibited a significantly greater improvement in insulin sensitivity and oDI versus metformin alone and versus metformin plus lifestyle; these improvements were sustained over 48 months of TODAY. Irrespective of treatment, those who failed to maintain glycemic control had significantly lower β-cell function (∼50%), higher fasting glucose concentration, and higher HbA(1c) at randomization compared with those who did not fail. CONCLUSIONS: The beneficial change in insulin sensitivity and the resultant lower burden on β-cell function achieved in the first 6 months with metformin plus rosiglitazone appear to be responsible for its superior glycemic durability over metformin alone and metformin plus lifestyle. However, initial β-cell reserve and HbA(1c) at randomization are independent predictors of glycemic durability. Therefore, efforts to preserve β-cell function before significant loss occurs and to reduce HbA(1c) may be beneficial in the treatment of youth with type 2 diabetes.